The Effects of Exogenous Basic Fibroblast Growth Factor on Intrasynovial Flexor Tendon Healing in a Canine Model - Thomopoulos, Stavros (Journal of Bone and Joint Surgery, Inc., 2010)
BACKGROUND: Studies have demonstrated that flexor tendon repair strength fails to increase in the first three weeks following suturing of the tendon, a finding that correlates closely with the timing of many clinical failures. The application of growth factors holds promise for improving the tendon-repair response and obviating failure in the initial three weeks. METHODS: The effects of basic fibroblast growth factor on flexor tendon healing were evaluated with use of a canine model. Operative repair followed by the sustained delivery of basic fibroblast growth factor, at two different doses, was compared with operative repair alone. Histological, biochemical, and biomechanical methods were used to evaluate the tendons twenty-one days after repair. RESULTS: Vascularity, cellularity, and adhesion formation were increased in the tendons that received basic fibroblast growth factor as compared with the tendons that received operative repair alone. DNA concentration was increased in the tendons that received 1000 ng of basic fibroblast growth factor (mean and standard deviation, 5.7 ± 0.7 μg/mg) as compared with the tendons that received 500 ng of basic fibroblast growth factor (3.8 ± 0.7 μg/mg) and the matched control tendons that received operative repair alone (4.5 ± 0.9 μg/mg). Tendons that were treated with basic fibroblast growth factor had a lower ratio of type-I collagen to type-III collagen, indicating increased scar formation compared with that seen in tendons that received operative repair alone (3.0 ± 1.6 in the group that received 500-ng basic fibroblast growth factor compared with 4.3 ± 1.0 in the paired control group that received operative repair alone, and 3.4 ± 0.6 in the group that received 1000-ng basic fibroblast growth factor compared with 4.5 ± 1.9 in the paired control group that received operative repair alone). Consistent with the increases in adhesion formation that were seen in tendons treated with basic fibroblast growth factor, the range of motion was reduced in the group that received the higher dose of basic fibroblast growth factor than it was in the paired control group that received operative repair alone (16.6° ± 9.4° in the group that received 500 ng basic fibroblast growth factor, 13.4° ± 6.1° in the paired control group that received operative repair alone, and 29.2° ± 5.8° in the normal group [i.e., the group of corresponding, uninjured tendons from the contralateral forelimb]; and 15.0° ± 3.8° in the group that received 1000 ng basic fibroblast growth factor, 19.3° ± 5.5° in the paired control group that received operative repair alone, and 29.0° ± 8.8° in the normal group). There were no significant differences in tendon excursion or tensile mechanical properties between the groups that were treated with basic fibroblast growth factor and the groups that received operative repair alone. CONCLUSIONS: Although basic fibroblast growth factor accelerated the cell-proliferation phase of tendon healing, it also promoted neovascularization and inflammation in the earliest stages following the suturing of the tendon. Despite a substantial biologic response, the administration of basic fibroblast growth factor failed to produce improvements in either the mechanical or functional properties of the repair. Rather, increased cellular activity resulted in peritendinous scar formation and diminished range of motion. CLINICAL RELEVANCE: Despite success in stimulating cellular proliferation and matrix synthesis in flexor tendons through the application of a growth factor in a clinically relevant animal model, no significant improvements were noted in either functional or structural properties. Therefore, as applied in this model, basic fibroblast growth factor is not recommended for intrasynovial flexor tendon repair.